2012
DOI: 10.1371/journal.pone.0035955
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Overexposure Increases the Expression of VGLUT-2 Mediated Projections from the Lateral Vestibular Nucleus to the Dorsal Cochlear Nucleus

Abstract: The dorsal cochlear nucleus (DCN) is a first relay of the central auditory system as well as a site for integration of multimodal information. Vesicular glutamate transporters VGLUT-1 and VGLUT-2 selectively package glutamate into synaptic vesicles and are found to have different patterns of organization in the DCN. Whereas auditory nerve fibers predominantly co-label with VGLUT-1, somatosensory inputs predominantly co-label with VGLUT-2. Here, we used retrograde and anterograde transport of fluorescent conjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 91 publications
6
54
0
Order By: Relevance
“…For auditory processing, early convergence occurs at the first synaptic levels in the mammalian brain stem: anatomical studies in guinea pigs (Burian and Gstoettner 1988;Burian et al 1989Burian et al , 1991, gerbils (Kevetter andPerachio 1986, 1989), rats (Barker et al 2012), and macaque monkeys (Newlands and Perachio 2003) have shown that the vestibular nerve and lateral vestibular nucleus project to the cochlear nucleus, the first station of the central auditory pathway. Proprioceptive/efference copy input is present already in the vestibular nuclei , as are visual motion signals (Waespe and Henn 1977), so vestibular pathways are likely to also convey proprioceptive and visual information.…”
Section: Auditory Vs Multimodal Spatial Representations: Behavioral mentioning
confidence: 99%
“…For auditory processing, early convergence occurs at the first synaptic levels in the mammalian brain stem: anatomical studies in guinea pigs (Burian and Gstoettner 1988;Burian et al 1989Burian et al , 1991, gerbils (Kevetter andPerachio 1986, 1989), rats (Barker et al 2012), and macaque monkeys (Newlands and Perachio 2003) have shown that the vestibular nerve and lateral vestibular nucleus project to the cochlear nucleus, the first station of the central auditory pathway. Proprioceptive/efference copy input is present already in the vestibular nuclei , as are visual motion signals (Waespe and Henn 1977), so vestibular pathways are likely to also convey proprioceptive and visual information.…”
Section: Auditory Vs Multimodal Spatial Representations: Behavioral mentioning
confidence: 99%
“…The vestibular inputs to the DCN are well documented (9,(26)(27)(28)(29). What role do they play in DCN processing?…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly prominent in the dorsal cochlear nucleus (DCN), which is known to integrate non-auditory sensory information and receives glutamatergic inputs from different parts of the vestibular nuclei (Barker et al, 2012). In gerbils and guinea pigs, there are also connections between the saccule and all auditory nuclei (Kevetter and Perachio, 1989;Gstoettner et al, 1991).…”
Section: Interaction Between Auditory and Vestibular Pathwaysmentioning
confidence: 99%